OXA-1 β-lactamase and non-susceptibility to penicillin/β-lactamase inhibitor combinations among ESBL-producing Escherichia coli. (2nd November 2018) - Livermore, David M; Day, Michaela; Cleary, Paul; Hopkins, Katie L; Toleman, Mark A; Wareham, David W; Wiuff, Camilla; Doumith, Michel; Woodford, Neil
Abstract: Background: ESBL-producing Escherichia coli have expanded globally since the turn of the century and present a major public health issue. Their in vitro susceptibility to penicillin/inhibitor combinations is variable, and clinical use of these combinations against ESBL producers remains controversial. We hypothesized that this variability related to co-production of OXA-1 penicillinase. Methods: During a national study we collected 293 ESBL-producing E. coli from bacteraemias, determined MICs by BSAC agar dilution, and undertook genomic sequencing with Illumina methodology. Results: The collection was dominated by ST131 ( n = 188 isolates, 64.2%) and bla CTX-M-15 (present in 229 isolates, 78.2%); over half the isolates (159/293, 54.3%) were ST131 with bla CTX-M-15 . bla OXA-1 was found in 149 ESBL producers (50.9%) and bla TEM-1/191 in 137 (46.8%). Irrespective of whether all isolates were considered, or ST131 alone, there were strong associations ( P < 0.001) between co-carriage of bla OXA-1 and reduced susceptibility to penicillin/inhibitor combinations, whereas there was no significant association with co-carriage of bla TEM-1/191 . For piperacillin/tazobactam the modal MIC rose from 2 mg/L in the absence of bla OXA-1 to 8 or 16 mg/L in its presence; for co-amoxiclav the shift was smaller, from 4 or 8 to 16 mg/L, but crossed the breakpoint. bla OXA-1 was strongly associated with co-carriage also of aac(6′)-Ib-cr, which compromises amikacin and tobramycin. Conclusions: Co-carriage of OXA-1, a penicillinase with weak affinity for inhibitors, is a major correlate of resistance to piperacillin/tazobactam and co-amoxiclav in E. coli and is commonly associated with co-carriage of aac(6′)-Ib-cr, which narrows aminoglycoside options.